2016
DOI: 10.1071/aj15018
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder trust in the Queensland CSG industry

Abstract: Stakeholder trust is pivotal to the social licence to operate and a source of competitive advantage for firms. While managing trust with stakeholders is recognised as a critical management competency and central to delivering coal seam gas (CSG) strategy, to date there has been little examination of stakeholder trust. This research examined the drivers and levels of trust in the CSG companies and industry from the perspective of core CSG stakeholder groups, and identified what stakeholders perceive to be criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…As CSG developments are often located on prime agricultural land, land use conflict and stakeholder trust is a concern for gas operators [93]. A lack of trust in the CSG operator is quite often the most significant social issue which underpins many of the other concerns affecting the progress of promoting coexistence between agribased industries and CSG industry [91]. Land access agreements and their associated 'confidentiality clauses' can contribute to the distrust with CSG operators and regulatory bodies.…”
Section: Agricultural Value Chain 214mentioning
confidence: 99%
See 1 more Smart Citation
“…As CSG developments are often located on prime agricultural land, land use conflict and stakeholder trust is a concern for gas operators [93]. A lack of trust in the CSG operator is quite often the most significant social issue which underpins many of the other concerns affecting the progress of promoting coexistence between agribased industries and CSG industry [91]. Land access agreements and their associated 'confidentiality clauses' can contribute to the distrust with CSG operators and regulatory bodies.…”
Section: Agricultural Value Chain 214mentioning
confidence: 99%
“…However, the progress of amalgamating agricultural industries with the CSG industry has been slow [9]. There is cumulative effect of coexisting CSG developments in close proximity to agricultural developments that are complicated by community attitudes, local industries, environmental assets, and regulations [91,92].…”
Section: Agricultural Value Chain 214mentioning
confidence: 99%
“…In Australia and internationally, research points to trust between a company and its stakeholders being at the heart of the social licence process (Gillespie et al, 2016;Warhurst, 2001;Williams & Walton, 2013;Zhang et al, 2015). That trust acts as a driver of social acceptance has been established in many contexts, including carbon capture and storage, wind farms, onshore and offshore mining, CSG development, gene technologies, food technologies, nuclear power, and recycled water (e.g., Eiser, Miles, & Frewer, 2002;Greenberg, 2014;Hall, Ashworth, & DevineWright, 2013;Mason et al, 2014;Ross et al, 2014;Siegrist, 2000).…”
Section: Trust and Social Acceptancementioning
confidence: 99%
“…Gillespie, Bond, Downs, and Staggs (2016), in a study of the Queensland coal seam gas (CSG) industry involving 145 interviews and 561 surveys with stakeholders, stated that " [stakeholder] trust is pivotal to the social licence to operate" (p. 1). Similarly, in large-scale studies on SLO focusing on the acceptance of mining at national levels across Australia, Chile, and China, Zhang et al (2015) found trust, in every country, to be a critical driver of social acceptance.…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation